Optimasi Berat Struktur Rangka Batang Pada Jembatan Baja Terhadap Variasi Bentang - Indriyati, Eva Wahyu (Jenderal Soedirman University, 2008)
This research was compared some types of trusses for some length of stellbridges. To support an equal loads, each type of truss have most optimal dimension to the each type. Aspect that compared at this research is Â weight of stell that required to a type of truss. Types of trusses that compared at this research are Pratt, Howe,Â Warren (with verticals), Parker, and K-Truss.Â From this research we can know that the most optimal trussfor each length of stell bridge. Parker is a type of truss that able to be used for all length of stell bridge that evaluated in this research, that are 30 m, 50 m, 70 m, and 100 m. This type of truss have the lightest own weight for all length if compared with other types of trusses.